Daptomycin: Physicochemical, Analytical, and Pharmacological Properties - Totoli, Eliane Gandolpho [UNESP]; Garg, Sanjay; Nunes Salgado, Herida Regina [UNESP] (Lippincott Williams & Wilkins, 2015)
Daptomycin is the first approved member of a new class of antimicrobials, the cyclic lipopeptides, and presents selective action against gram-positive bacteria, including methicillin- and vancomycin-resistant strains. Considering that resistance to daptomycin is rare, the drug has become very important for current clinical practice. This review covers daptomycin's physicochemical characteristics, antibacterial spectrum, mechanism of action, pharmacokinetics, clinical applications, side effects, drug interactions, and the analytical methods used to measure daptomycin in pharmaceutical products and biologic samples. Special attention has been given to therapeutic drug monitoring reports, as studies have shown its highly variable pharmacokinetics in specific circumstances, such as in patients suffering from critical illness, morbid obesity, severe sepsis, and kidney injury. For the same reason, methods described for therapeutic drug monitoring of daptomycin in the special patient population have been reviewed. In addition, the review presents a discussion of environmentally friendly analytical methods for daptomycin, which are necessary to reduce the impact of our activities on the environment. However, it was observed that there is a gap in the literature in this regard and further research involving the development of green methodologies for the analysis of daptomycin is necessary. The review will be useful to the clinical community in assisting with the responsible use of daptomycin, which is critical to prevent the emergence of resistant strains.
Keywords: daptomycin; cyclic lipopeptides; analytical methods; resistant strains; antimicrobial